1990
DOI: 10.12938/bifidus1982.9.1_27
|View full text |Cite
|
Sign up to set email alerts
|

Close Association of Streptococcus sanguis Uncommon Serotypes with Behcet's Disease

Abstract: This is a description of the role of Streptococcus sanguis in the oral flora of patients with Behcet's disease (BD) in contrast to the flora of healthy controls. The proportion of S. sanguis in the flora of patients with BD was always higher than that of healthy and disease controls. The types of S. sanguis in the oral flora of the BD patients were uncommon ones. Agglutinating antibody titers against isolated strains of S. sanguis were higher in BD patients than in controls. When S. sanguis antigens were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…The patients show hypersensitivity in skin tests with streptococcal antigens, and sometimes symptoms typical of BD are provoked by an injection of these antigens (16). We found that the proportion of Streptococcus sanguis in the oral flora of BD patients significantly increased as compared with the controls and that the antigenicity of S. sanguis strains isolated from BD was different from that of the three type and reference strains of ATCC (ATCC10556T, ATCC10557, and ATCC10558T) as well as the S. sanguis strains isolated from patients with Kawasaki disease (designated as MCLS-1 and MCLS-2) (9,15 (3). They found that the cultures which were considered to be S. sanguisfrom their biochemical properties could be divided into two genetic groups (groups 1 and 3).…”
mentioning
confidence: 82%
“…The patients show hypersensitivity in skin tests with streptococcal antigens, and sometimes symptoms typical of BD are provoked by an injection of these antigens (16). We found that the proportion of Streptococcus sanguis in the oral flora of BD patients significantly increased as compared with the controls and that the antigenicity of S. sanguis strains isolated from BD was different from that of the three type and reference strains of ATCC (ATCC10556T, ATCC10557, and ATCC10558T) as well as the S. sanguis strains isolated from patients with Kawasaki disease (designated as MCLS-1 and MCLS-2) (9,15 (3). They found that the cultures which were considered to be S. sanguisfrom their biochemical properties could be divided into two genetic groups (groups 1 and 3).…”
mentioning
confidence: 82%
“…Isogai et al (12) reported that the flora of BD patients showed a greater proportion of S. sanguinis. In addition, they reported that an uncommon type of S. sanguinis was found in all BD cases.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the oral health is impaired in BD patients with the disease severity [11][12][13]15,16] . The antibodies against S. sanguinis showed cross reactivity with the synthetic peptides of HSP-65 derived from the There are some reports that BD patients associated with HLA-B51 show much stronger reaction to "Pathergy test".…”
Section: Hypersensitivity Against S Sanguinismentioning
confidence: 99%
“…Although the actual etiology of BD is still unclear, the pathogenesis has been generally clearer by the etiological studies based on the genetic intrinsic factors and extrinsic triggering factors [5][6][7][8][9][10][11][12][13][14][15][16] . As one of the triggering factors, the oral unhygienic condition may be suspected, because periodontitis, decayed teeth, chronic tonsillitis, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation